Three-Dimensional Custom-Made Titanium Ribs for Reconstruction of a Large Chest Wall Defect - Isabel Simal; Maria Antonia García-Casillas; Julio Arturo Cerdá; Óscar Riquelme; Concepción Lorca-García; Laura Pérez-Egido; Beatriz Fernández-Bautista; Manuel de la Torre; Juan Carlos de Agustín (Georg Thieme Verlag KG, 2016)
Reconstruction of large chest wall defects always demand surgeons of having lots of means available (both materials and resourceful) to apply a cover to chest wall defects which can range from a few centimeters to the lack of a few entire ribs. In this study, we present the case of a teenager who suffered from a complete resection of three ribs because of Ewing sarcoma dependent on the sixth rib. Given the size of the defect, a multidisciplinary approach was chosen to provide rigid and soft tissue coverage and minimal functional and aesthetic impact. Custom-made titanium implants were designed based on three-dimensional computed tomography scan reconstruction. The surgical specimen via a left lateral thoracotomy (fifth, sixth, and seventh entire ribs) was resected, leaving a defect of 35 × 12 × 6 cm. A Gore-Tex patch (W. L. Gore & Associates, Arizona, United States) was placed and, after that, the implants were anchored to the posterior fragment of the healthy ribs and to the costal cartilage anteriorly. Finally, the surgical site was covered with a latissimus dorsi flap. The postoperative course was uneventful. After 9 months of follow-up, the patient has full mobility. This case shows that the implant of custom-made ribs, combined with other techniques, is a good surgical choice for reconstruction of large chest wall defects. The implant of custom-made ribs, combined with other techniques, is a good surgical choice for reconstruction of large chest wall defects.